2002
DOI: 10.1098/rspb.2001.1952
|View full text |Cite
|
Sign up to set email alerts
|

Changes in women's sexual interests and their partner's mate–retention tactics across the menstrual cycle: evidence for shifting conflicts of interest

Abstract: Because ancestral women could have obtained genetic benefits through extra-pair sex only near ovulation, but paid costs of extra-pair sex throughout the cycle, one might expect selection to have shaped female interest in partners, other than primary partners, to be greater near ovulation than during the luteal phase. Because men would have paid heavier costs if their partners had extra-pair sex near ovulation, one might also expect selection to have shaped males' efforts to track their primary partners' wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
224
4
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(264 citation statements)
references
References 46 publications
18
224
4
8
Order By: Relevance
“…show an increase in jealous mate-guarding for women near ovulation (Gangestad et al, 2002), which is of evolutionary importance, given that ovulation reflects a period in which a man's reproductive probability may be compromised by partner defection (Buss & Haselton, 2005). Although speculative, when considered in the context of this evidence, the present findings that men on T show a significantly greater preference for feminine female faces in the short-term versus long-term contexts (but no difference in context preference when on placebo) could suggest the possibility that T may increase men's sensitivity to infidelity cues, perhaps triggering careful decision-making regarding the trade-off between a healthy partner with good genes (i.e., feminine faces), and personality/potential for defection (i.e., a more masculine face offering reduced likelihood of cheating) when it comes to selecting a long-term mate.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…show an increase in jealous mate-guarding for women near ovulation (Gangestad et al, 2002), which is of evolutionary importance, given that ovulation reflects a period in which a man's reproductive probability may be compromised by partner defection (Buss & Haselton, 2005). Although speculative, when considered in the context of this evidence, the present findings that men on T show a significantly greater preference for feminine female faces in the short-term versus long-term contexts (but no difference in context preference when on placebo) could suggest the possibility that T may increase men's sensitivity to infidelity cues, perhaps triggering careful decision-making regarding the trade-off between a healthy partner with good genes (i.e., feminine faces), and personality/potential for defection (i.e., a more masculine face offering reduced likelihood of cheating) when it comes to selecting a long-term mate.…”
Section: Discussionmentioning
confidence: 97%
“…Feminine female faces, both as composites and real faces, are accurately rated by men as having a more unrestricted sociosexuality (i.e., more likely to pursue short-term relationships; Boothroyd et al, 2011;Boothroyd et al, 2008; but see Campbell et al, 2009), and near ovulation, some women report a greater sex drive, as well as interest in, or fantasy about, extra-pair partners (Gangestad et al, 2002;Gangestad et al, 2010;Haselton & Gangestad, 2006;see Gangestad & Thornhill, 2008, for review). Further, men…”
Section: Discussionmentioning
confidence: 99%
“…Despite the vast number of functional neuroimaging studies, surprisingly little research has investigated the neural basis of sex differences in brain activation patterns underlying cognitive-affective processing and how these differences might be modulated by the menstrual cycle. Studies have reported that female preference for male characteristics varies with the probability of conception across the menstrual cycle, with women manifesting more attraction to men with masculine traits during the late follicular phase of the menstrual cycle (when fertility is high), than at other times (Jones et al, 2005a andPenton-Voak et al, 1999) These studies support the existence of beneficial adaptations whereby ancestral females increased their reproductive success by increasing attraction to masculine traits in men when fertility probability was high (Penton-Voak et al, 1999) and increasing preferences for people believed to be trustworthy (DeBruine et al, 2005), to be free of contagion (Fessler, 2002;Flaxman and Sherman, 2000;Jones et al, 2005b) and to display social cues associated with relationship commitment (Gangestad et al, 2002) when fertility had a low probability. Protopopescu et al(2005) reported that inhibitory control does vary across the cycle but neuroscientists have yet to determine if this modulation is stimulus-specific.…”
Section: Introductionmentioning
confidence: 70%
“…For instance, during the follicular phase, heterosexual women reported more interest in sex (Schreiner-Engel, Schiavi, Smith, & White, 1981;Slob, Bax, Hop, Rowland, & van der Werff ten Bosch, 1996;Stanislaw & Rice, 1988;Zillmann, Schweitzer, & Mundorf, 1995) and increased sexual desire in diary studies (Bancroft, Sanders, Davidson, & Warner, 1983;Dennerstein et al, 1994). During the ovulatory phase heterosexual women were more likely to initiate sexual intercourse (Adam, Gold, & Burt, 1978;Bullivant et al, 2004;Van Goozen, Wiegant, Endert, 8 Helmond, & Van de Poll, 1997) ; reported more auto-sexual activity (Harvey, 1987); were more sexually aroused by erotic films (Slob, Ernste, & van der Werff ten Bosch, 1991); rated men other than their current partner as more sexually attractive (Larson, Pillsworth, & Haselton, 2012); and were more prone to fantasize about or have sexual intercourse with men other than their primary partners (Gangestad, Thornhill, & Garver, 2002). One study using eye tracking reported an increase in mean pupil diameter for sexually significant stimuli of participants' actual sexual partners during the ovulatory phase (Laeng & Falkenberg, 2007).…”
Section: The Role Of Waist-to-hip Ratio and Menstrual Cycle Phasementioning
confidence: 99%